Cytotoxic and Anti-Inflammatory Metabolites from the Soft Coral Scleronephthya gracillimum - Jyh-Horng Sheu; Chang-Feng Dai; Yang-Chang Wu; Chih-Hua Chao; Zhi-Hong Wen; Chi-Hsin Hsu; Hui-Yu Fang (Marine Drugs, 2013)
Five new pregnane-type steroids, sclerosteroids J–N (1–5), and a diterpenoid with a new chemotype 3-methyl-5-(10′-acetoxy-2′,6′,10′-trimethylundecyl)-2-penten-5-olide (6), have been isolated from a soft coral Scleronephthya gracillimum. The structures of the metabolites were determined by extensive spectroscopic analysis. Compound 4 exhibited cytotoxicity against HepG2, A549, and MDA-MB-231 cancer cell lines. Furthermore, steroids 2 and 4 were found to significantly inhibit the accumulation of the pro-inflammatory iNOS protein, and 1, 2, 4 and 5 could effectively reduce the accumulation of COX-2 protein in LPS-stimulated RAW264.7 macrophage cells.